Internal adaptation assessment of implant infrastructures manufactured through five different techniques (heat-press, milling, lost wax, calcinable cylinder, and CAD/Waxx®): an in vitro pilot study - Sartori, Régis; Fernandes, Juliana Campos Hasse; Fernandes, Gustavo Vicentis Oliveira; Joly, Julio Cesar (Frontiers in Dental Medicine, 2024)
Introduction The aim of this study was to evaluate the fit performance of implant infrastructures manufactured by five different techniques: heat-press (IPS), milling (ZIR), lost wax (CER), calcinable cylinder (CAL), and CAD/Waxx® (CAD). Methods The methodology was based on the Replica Technique, which can simulate and evaluate the fit of the infrastructure on the implant component. Thus, each infrastructure was internally filled with low-viscosity silicone addition and seated on the component until its final setting, obtaining the replica of the cementation space. After removing the coping containing the silicone film, light-density silicone was inserted addition in place of the components, and in its surroundings, condensation silicone was applied, establishing support for the assembly. The joint was sectioned mesiodistally, photographed, and analyzed in image processing software in order to measure the thickness of the interface infrastructure/implant at five different areas: marginal opening (M), gingival-axial angle (G-A), axial region (A), axial-occlusal angle (A-O) and occlusal surface (O). Results The lowest and the highest average thickness between groups was, respectively, IPS: 187.5 μm and CAD: 221.6 μm, with statistically significant differences (p < 0.01) among all five groups; the lowest and the highest average of all groups in each point was, respectively, A: 99.86 μm and O: 279.78 μm. The IPS group exhibited the lowest value of the internal space of the infrastructure on the implant. The marginal region of all groups demonstrated a correlation with the findings in the literature, except the CAL group; otherwise, the occlusal region and the angles A-O and G-A exhibited values beyond that expected. Discussion It was possible to conclude that the five infrastructure groups presented different adaptations, suggesting possible interference in the internal spaces due to the manufacturing infrastructure processes.